2021
DOI: 10.33715/inonusaglik.812109
|View full text |Cite
|
Sign up to set email alerts
|

Pandemi̇ Dönemi̇nde Üni̇versi̇te Öğrenci̇leri̇ni̇n Çevri̇mi̇çi̇ Öğrenmeye Hazirbulunuşluklarinin Ve Uzaktan Eği̇ti̇me İli̇şki̇n Deneyi̇mleri̇ni̇n Değerlendi̇ri̇lmesi̇

Abstract: COVID-19 pandemisi, eğitim alanında teknolojinin kullanımını zorunlu hale getirmiş, uzaktan eğitim ve çevrimiçi öğrenme kavramlarını tekrar gündeme getirmiştir. Tanımlayıcı tipteki bu araştırmanın evrenini, bir vakıf üniversitesinin öğrencileri oluşturdu. Online anket ile öğrencilere veri toplama formları ulaştırıldı, katılmaya gönüllü olan ve formu eksiksiz dolduran 435 öğrencinin verileri ile çalışma tamamlandı. Veriler, Öğrenci Tanıtıcı Bilgi Formu ve Çevrimiçi Öğrenme Hazır Bulunuşluk Ölçeği (ÇÖHBÖ) kullan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…These limitations are; problems occuring in the delivery of some lessons that require practice through the online education system, the lack of face-to-face education in the online education program and therefore the motivation of the students negatively affected, and the students who are unfamiliar with the use of technology encounter difficulties in learning. 12 The pandemic process; it seems to affect students to a great extent. It has been observed that students have a fear of losing their manual skills, causing anxiety about their long-term plans and anxiety about exams.…”
Section: Discussionmentioning
confidence: 99%
“…These limitations are; problems occuring in the delivery of some lessons that require practice through the online education system, the lack of face-to-face education in the online education program and therefore the motivation of the students negatively affected, and the students who are unfamiliar with the use of technology encounter difficulties in learning. 12 The pandemic process; it seems to affect students to a great extent. It has been observed that students have a fear of losing their manual skills, causing anxiety about their long-term plans and anxiety about exams.…”
Section: Discussionmentioning
confidence: 99%